A Participação Social no Processo de Planejamento Urbano: Um Estudo sobre o Plano Diretor Participativo do Município de Santa Rita - PB - Aguiar, José Ariosvaldo dos Anjos (2012)
The new rules of urban policy in the Brazil, down from the 1988 Constitution and regulated by the City Statute (2001), established a mandatory participation of civil society in the drafting of municipal master plans, which have become the basic tool for national policy in urban development. This study aims to analyze at what level is the civil society participation, particularly the social popular segments at the spaces for dialogue established in the drafting of the Santa Rita - PB Participatory Master Plan, and assess to what extent the proposals were incorporated in the Law of this Plan. In order to assess the social participation in various stages of Master Plan s preparation, studies on levels of social participation were adopted, related to the degree of empowerment and decision-making power of the social sectors, on their relationship with the public sector. In the development of research, a quantitative and qualitative approach was adopted, from documentary records and interviews, also using the technique of content analysis. As a result, it was found that in various stages of Santa Rita Participatory Master Plan, social participation took place at various levels, ranging from situations of non-participation to moments that occurred some participation of the social popular segments. This demonstrates that local social organizations still have a long way to go in order to have a more effective participation in decision-making processes, relating to the planning and management of urban policies in Santa Rita county, from the perspective of a citizen participation, an effective and democratic exercise of a society with rights, in order to build a more just and democratic city, a city of all.